Effect of Long-Distance Running on Inter-segment Foot Kinematics and Ground Reaction Forces: A Preliminary Study - Li, Jialin; Song, Yang; Xuan, Rongrong; Sun, Dong; Teo, Ee-Chon; Bíró, István; Gu, Yaodong (Frontiers in Bioengineering and Biotechnology, 2022)
Long-distance running has gained massive popularity in recent years, yet the intra-foot adaptations during this event remain unclear. This study aimed to examine the kinematic and ground reaction force alterations induced within the foot following a 5 and 10 km run using the Oxford Foot Model Ten marathon-experienced recreational runners participated in this study. Five-kilometer running led to more rearfoot dorsiflexion, rearfoot eversion, and rearfoot rotation while less forefoot plantarflexion during the stance phase. Increased rearfoot plantarflexion, while decreased forefoot plantarflexion, supination, adduction, and hallux plantarflexion were observed at 10 km. In addition, the forefoot space of footwear was found to play a role in hallux kinematics. Concerning GRFs, only a lesser propulsive force was presented after a 10 km run. Findings of this study showed that 5 km of running would induce excessive foot motion while 10 km of running may gradually change the foot posture and lead to reduced propulsive forces, which could potentially increase the risks of running-related injuries (RRI) due to overuse or fatigue. Nevertheless, further research is warranted, and this study could be used as a preliminary reference to evaluate and predict foot running-related injuries.